Correction for effect of temperature-dependent diffusivity on temperature-sensitive-paint heat-flux measurement. (July 2019) - Liu, Tianshu; Montefort, Javier; Schick, Nathan; Stanfield, Scott; Palluconi, Steve; Crafton, Jim
Highlights: A simple method is developed for correction of the effect of the temperature-dependent thermal diffusivity on temperature-sensitive-paint (TSP) heat flux measurements. This method is validated through simulations. A correction factor is introduced. Abstract: A simple method is developed for correcting the effect of the temperature-dependent thermal diffusivity on temperature-sensitive-paint (TSP) heat flux measurements in hypersonic wind tunnels. The relation between the heat flux obtained using the constant thermal diffusivity and the heat flux obtained using the temperature-dependent diffusivity is discussed based on an analysis of the nonlinear heat conduction equation. The non-dimensional correction factor is introduced and modeled as an approximate function of the measured surface temperature for the monotonically increasing heat flux histories, which can be determined in situ using the data at several selected points. The corrected heat flux field is obtained by multiplying the correction factor field with the heat flux field obtained using the analytical inverse heat transfer method for constant thermal properties. This method is validated through simulations.